Vaccines and Therapeutics Against Hantaviruses - Liu, Rongrong; Ma, Hongwei; Shu, Jiayi; Zhang, Qiang; Han, Mingwei; Liu, Ziyu; Jin, Xia; Zhang, Fanglin; Wu, Xingan (Frontiers in Microbiology, 2020)
Hantaviruses (HVs) are rodent transmitted viruses that can cause hemorrhagic fever with renal syndrome (HFRS) in Eurasia and hantavirus cardio-pulmonary syndrome (HCPS)in the Americas. Together, these viruses cause approximately 200,000humaninfections annually worldwide in recent years, with case fatality rate of 5-15%for HFRS and up to 40% for HCPS. There are currently no effective treatment available for either HFRS or HCPS. The only vaccines licensed for use in Republic of Korea and China are based on inactivated whole Seoul virus (SEOV) and Hantaan virus(HTNV), but the protective efficacy of these vaccines are uncertain. To a large extent, the immune correlates of protection against Hantavirus are not known. In this review, we summarized the epidemiology, virology, and pathogenesis of four HFRS causing viruses, HTNV, SEOV, PUUV (Puumala virus), and DOBV (Dobrava-Belgrade virus); and two HCPS causing viruses, ANDV (Andes virus) and SNV (Sin Nombre virus); and then discussed the existing knowledge on vaccine and therapeutics against these diseases. We think these information will shed lights on the rational development of new vaccines and treatment.